(untitled) (Proceedings of the International Conference on Education, 2025)
Development of technology cannot be avoided, so it will give an impact on all aspects of life, including the field of education. Learning using technology can make learning more effective and efficient. However, technological developments also have a negative impact on culture, because access to other cultures is easier. This makes it difficult to preserve one’s own culture. Apart from that, technology also helps the process of learning mathematics, which is known to be abstract, to become more realistic with visualization and a more real approach. This research aims to analyze the Etno-RME approach to learning basic algebra concepts with the help of ICT. The approach used in this research is fenomenology qualitative. The data in this research was obtained using observation and interview techniques with class VII students who applied basic algebra concept learning using the Etno-RME approach. The data analysis used in this research uses the Miles & Huberman data analysis technique with stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that the application of mathematics learning uses a contextual approach based on Borobudur temple culture. The learning process is designed in accordance with the learning obstacles experienced by students before, during, and after the implementation of instruction. Designed learning can create more effective and innovative learning situations to improve student’s conceptual understanding.